Caddisflies (Trichoptera) of the Hungarian section of river Tisa - Nógrádi Sára (Tiscia monograph series, 1999)
77 species occur along the river and its upper tributaries. Only 26 of them occur along the middle and lower sections of the river. The upper section and especially one of the tributaries (i.e. river Túr) had the most diverse caddisfly community. Both distribution data and the results of phenological examinations are presented. Stactobiella risi Felber lives only in the northeastern part of the Plain, in river Tisa and its water system.